Heat transfer analysis in underground cable tunnel using computational fluid dynamics / Janash S.Pathamnathan - Janash, S.Pathamnathan (2018)
The key concern of this study is to develop an underground cable tunnel ventilation system using the analytical method to determine the best inlet velocity and air flow to create an environment that is close to the outside ambient air. This is done in order for people to occupy the tunnel in for repair and maintenance work. For the analysis of the 90m long tunnel with rectangular and circular manholes, the Computational Fluid Dynamics (CFD)for steady state conditions was be used. The CFD software ANSIS Fluent was used in the analysis of the tunnel system. This tunnel will house the XLPE 132 IC 1200mm2, the cable will be routed in a trefoil configuration per-circuit and there will be 4 circuits running in this tunnel. Using various airflow configurations, the study was conducted to determine the best internal temperature conditions at peak operation conditions. The heat generated by the cable is calculated to be 58.540C however for the purpose of the simulation the temperature is assumed to 600C. The ambient temperature which is given more focus will be 330C.This is because according to the meteorological department for Petaling Jaya area the average temperature is 330C. However, there were two other temperatures also was used in the analysis with the same variant of air flows. This was done to observe the effects of the velocity on this various temperature which were higher and lower than the main temperature in question. From the total analysis that was carried out it can be determined that the most suitable inlet air velocity is 4m/s with the air flow of 15000CFM. With this configuration the internal ambient temperature of 34.740C can be achieved. This temperature is conducive enough for repair and maintenance work to be carried in the cable tunnel.